Liberation At Work: Workload, Work-Related Stress, And Turnover Intention Among Generation Z - Dani Nurhilali Firmansyah; Herdiyan Maulana; Lussy Dwiutami Wahyuni (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Turnover intention has become an increasingly important issue among Generation Z employees. As a generation that values work-life balance, flexibility, and supportive work environments, Generation Z tends to consider leaving an organization when experiencing excessive job demands and psychological pressure. This study aims to examine the influence of workload and job stress on turnover intention among Generation Z employees in Jakarta. This study employed a quantitative explanatory research design involving 108 Generation Z employees selected through purposive sampling. Data were collected using validated questionnaires measuring workload, job stress, and turnover intention. Multiple linear regression analysis was performed using JASP software. The findings indicate that workload has a positive and significant effect on turnover intention. Job stress also positively and significantly affects turnover intention. Furthermore, workload and job stress simultaneously have a significant influence on turnover intention among Generation Z employees in Jakarta. These findings suggest that excessive workload and psychological stress increase employees' intentions to leave their organizations. Therefore, organizations should develop effective workload management and stress reduction strategies to improve employee retention among Generation Z